POSTCOLONIALITY IN ERWIN CLARKSON GARRET’S THE DYAK CHIEF BALLAD - Nasrullah, Nasrullah; Arifin, M. Bahri (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
This research would analyze the postcoloniality of Erwin Clarkson Garret’s The Dyak Chief Ballad. This research using  the elements of poetry theory, poetry and history and postcolonial theory. The method of this research using structural approach and postcolonial analysis. This research analyze the elements of poetry, the translation into Bahasa Indonesia, the historical context of the poetry, and postcolonial aspect of the poetry is the elements. The result of this research are the identification of intrinsic elements of this ballad, the translation into Bahasa Indonesia, the historical context of this ballad that related to early first world war, and the representation of the native (the East) by the West.